Factors Affecting Abdominal Circumference in Adolescent Girls: Faktor-Faktor yang Berpengaruh terhadap Lingkar Perut pada Remaja Putri - Luthfiya, Lulu'; Pibriyanti, Kartika; Nabawiyah, Hafidhotun; Fathimah, Fathimah; Ummah, Safira Kholifatul (Amerta Nutrition, 2024)
Background: Central obesity was a health problem in Indonesia. One of indicator to find out central obesity was abdominal circumference. According to preliminary research, 28.4% of students had abdominal circumference >80 cm. Central obesity cause is multifactorial. Objectives: To identify factors related to abdominal circumference in adolescent girls. Methods: The design research was a cross-sectional. The total sample was 89 respondents, using the Lemeshow formula. The Sampling was taken by purposive sampling. The abdominal circumference data was measured by a metline. The percentage of body fat was analyzed with the Omron body fat analyzer. Food consumption patterns used Semi Quantitative Food Frequency (SQ-FFQ). Emotional overeating used the Adult Eating Behaviour Questionnaire (AEBQ), diet attitude, and oral control with the Eating Attitude Test (EAT)-26. The Data was analyzed by STATA 13 with the spearman test. Results: Relationship of BMI (p=0.000; r=0.677), percentage of body fat (p=0.000; r=0.56), kind of junk food (p=0.02; r=0.23). frequency of junk food (p=0.04; r=0.21), energy intake from junk food (p=0.0061, r=0.28), fat intake from junk food (p=0.018, r=0.24), total enery intake (p=0.036; r=0.222), total fat intake (p=0.01; r=0.24); total fiber (p=0.17; r=0.14); overeating (p=0.018, r=0.25); diet attitude (p=0.000; r=-0.52), and oral control (p=0.0001; r=0.39) with abdominal circumference. Conclusions: There was a relationship between BMI, body fat percentage, junk food consumption pattern (type, frequency, amount of intake and fat), energy intake, fat intake, emotional overeating, diet attitude, and oral control of the abdominal circumference. There was no significant relationship between fiber intake and abdominal circumference.